2004
DOI: 10.1097/00004647-200412000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging and Somatosensory Evoked Potentials in Rats With a Neonatally Induced Freeze Lesion of the Somatosensory Cortex

Abstract: Summary:Brain plasticity is an important mechanism for functional recovery from a cerebral lesion. The authors aimed to visualize plasticity in adult rats with a neonatal freeze lesion in the somatosensory cortex using functional magnetic resonance imaging (fMRI), and hypothesized activation outside the primary projection area. A freeze lesion was induced in the right somatosensory cortex of newborn Wistar rats (n ‫ס‬ 12). Sham-operated animals (n ‫ס‬ 7) served as controls. After 6 or 7 months, a neurologic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(31 reference statements)
3
2
0
Order By: Relevance
“…Cortical evoked potentials recorded in this study had an average latency of 12.1 AE 1.6 ms which is consistent with Huttunen et al (2008), Koyanagi and Tator (1996) and Schwindt et al (2004) who report cortical evoked potentials occurring between 12 and 17 ms after forepaw stimulation under α-chloralose anaesthesia. There is greater variation in the magnitude of the evoked potential presented in literature which can be attributed to differing recording techniques.…”
Section: Do Recorded Signals From Cortex and Thalamus Match The Litersupporting
confidence: 91%
“…Cortical evoked potentials recorded in this study had an average latency of 12.1 AE 1.6 ms which is consistent with Huttunen et al (2008), Koyanagi and Tator (1996) and Schwindt et al (2004) who report cortical evoked potentials occurring between 12 and 17 ms after forepaw stimulation under α-chloralose anaesthesia. There is greater variation in the magnitude of the evoked potential presented in literature which can be attributed to differing recording techniques.…”
Section: Do Recorded Signals From Cortex and Thalamus Match The Litersupporting
confidence: 91%
“…Our results showed stimulus-driven fMRI modulation in the PMG. The finding that signals can be elicted from PMG is consistent with previous functional imaging studies of visual system in animals [Schwindt et al, 2004] and humans [Burneo et al, 2004;Innocenti et al, 2001;Janszky et al, 2003;Paetau et al, 2004].…”
Section: Discussionsupporting
confidence: 90%
“…Animal studies have demonstrated that PMG may show variable responses to stimulation in terms of activation and organization. Some studies have shown reduced activations with sensory stimulation [Schwindt et al, 2004], while other studies showed a disruption of cortical organization in the somatosensory cortex [Jacobs et al, 1999b;Rosen et al, 2001] and a disruption of retinotopic organization following lesions in the immature occipital cortex [Restrepo et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Latencies of electrically induced SSEPs in rats reported by others (Nashmi et al, 1997;Schlag et al, 2001;Schwindt et al, 2004) are similar to those recorded in our study (Table 2). We compared electrically induced SSEPs in parallel with M-SSEPs which revealed slightly (but not significantly) shorter latencies but similar amplitudes.…”
Section: M-ssep In Ratssupporting
confidence: 92%